2015
DOI: 10.1007/s00167-015-3614-8
|View full text |Cite
|
Sign up to set email alerts
|

Patellar instability: CT and MRI measurements and their correlation with internal derangement findings

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
2
40
1
4
Order By: Relevance
“…Three MR-based studies that used the same measurement technique described in the current study reported TT-TG distances of 14.6±4.6mm (n=109) 3 , 14.7±4.9mm (n=34) 8 , and 14.7±2.8mm (n=32). 46 In contrast, Dejour and Walch 13 studied subjects with a history of patellar dislocation using CT and and reported an average TT-TG distance of 20.0±1.6mm (n=110). 13 Based on these findings, TT-TG distances ≥15mm and ≥20mm have been proposed as the threshold for pathological categorization on MR and CT images, respectively, for patients with a history of patellar dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Three MR-based studies that used the same measurement technique described in the current study reported TT-TG distances of 14.6±4.6mm (n=109) 3 , 14.7±4.9mm (n=34) 8 , and 14.7±2.8mm (n=32). 46 In contrast, Dejour and Walch 13 studied subjects with a history of patellar dislocation using CT and and reported an average TT-TG distance of 20.0±1.6mm (n=110). 13 Based on these findings, TT-TG distances ≥15mm and ≥20mm have been proposed as the threshold for pathological categorization on MR and CT images, respectively, for patients with a history of patellar dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the inter-rater and intra-rater reliability of TT-TG measurement via MRI has been reported to be less than 10 percent. This study has shown that MRI is a reliable method for the evaluation of TT-TG [7,11,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…It is also very difficult to determine the deepest point of the trochlear groove, and for this reason, significant measurement errors may occur [6]. MRI can evaluate soft tissue at a higher accuracy and does not involve radiation, and therefore its use is recommended for the pathologic diagnosis of patellofemoral ligaments [7]. In the present study, we evaluated the reliability of MRI in the measurement of the TT-TG distance and determined the normal values for this distance in males and females from different age groups based on knee examination and MRI findings.…”
mentioning
confidence: 99%
“…These parameters provide us the severity of the deformity and it allows the surgeon to decide the best procedure [1] [4]. Dysplastic trochlea is shallow, flat or even convex.…”
Section: A Trochlear Dysplasiamentioning
confidence: 99%
“…There are some factors leading to patellar instability such as trochlear dysplasia, patellar tilt, patella alta and an excessive tibial tubercle-trochlear groove (TT-TG) distance [1][3] [4]. The MPFL rupture can be cited as a cause or a consequence, it depends if the dislocation occurs before or after the rupture.…”
Section: Introductionmentioning
confidence: 99%